Interlanguage pragmatic development : the study abroad context - Schauer, Gila A. (Continuum, 2009)
Gila Schauer's study of interlanguage pragmatic development in English is situated in the context of studying abroad. It is the first book-length study of a common occurrence worldwide, but one that has not received the focus it deserves. Schauer examines the interlanguage pragmatic development of German learners of English at a British University over the course of a year. The focus is not only on the learners' productive pragmatic development, but also on their pragmatic awareness, which is compared with their grammatical awareness. The analysis undertaken is both qualitative and quantitative, and the book draws some important conclusions relevant to the whole field of interlanguage pragmatics. It will be engaging reading for researchers and postgraduate studies in applied linguistics, especially those working on interlanguage and cross-cultural pragmatics, multilingualism and second language acquisition.